Um olhar bakhtiniano sobre a questão do dialogismo X monologismo: Macabéa e a linguagem no processo de (des)constituição do eu - Vale, Rosiney Aparecida Lopes do; Messias, Rozana Aparecida Lopes [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2014)
Bakhtin, during the development of his theories, focused matters concerned to language, also taking account of the vital importance of its role in the formation of men. Thus, he was concerned in treating language not only as a simple mean of communication among people, but also as a social and crucial activity for the development of human beings. According to that and regarding the Bakhtinian concepts of alterity and dialogism in this paper, we intend to verify some aspects related to Macabéa, the protagonist of the novel entitled A Hora da Estrela, by Clarice Lispector, as well as her communication with the outside world, via language, trying to clarify, into that process, elucidative elements which attest her diffi culty in interacting with the world that surrounds her, besides the consequent de(constitution) of her own identity.

Bakhtin, no desenvolvimento de suas teorias, concedeu especial atenção às questões relativas à linguagem, considerando também de fundamental importância o papel exercido pelo outro na formação do homem. Assim, mostrou-se preocupado em tratar a linguagem não como simples veículo de comunicação entre os homens, mas como uma atividade social de essencial importância para o desenvolvimento humano. Diante do exposto e em consonância com os conceitos de alteridade e dialogismo bakhtiniano, no presente trabalho, propomo-nos a verifi car alguns aspectos relativos à Macabéa, personagem da obra A hora da estrela, de Clarice Lispector, bem como seus contatos com o mundo, via linguagem, procurando nestes encontrar elementos elucidativos de sua difi culdade em interagir com o universo que a cerca e a consequente (des) constituição de sua identidade.
A Bakhtinian view on the issue of dialogism versus monologism: Macabéa and the language within the process of the (de)constitution of the “I”
Keywords: Bakhtin; Dialogism; Monologue; Otherness; Bakhtin; Dialogismo; Monologismo; Alteridade